Google Trends and Information Seeking Trend of COVID-19 in Indonesia - Putri Limilia; Benazir Bona Pratamawaty (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2020)
WHO has declared COVID-19 as a pandemic due to its rapid increase in cases outside China. COVID-19 has also affected a growing number of countries. However, the Indonesia government responded to the declaration in a not-serious manner, which has generated uncertainty circumstance among its public. This circumstance has driven people to consume information as much as they are possible to consume. This study aims to map out the trend of information-seeking concerning COVID-19 in Indonesia using Google Trends and to compare it to the information available on Indonesia's Ministry of Health official website from January until March. This study was descriptive quantitative, which used Google Trends as data collection tools. The research found that information seeking concerning COVID-19 has been increasing since the end of January. Government statements were found as the trigger of the information-seeking activity escalation and also served as the reason behind different information-seeking trends each month.